Relationship between Health Literacy and Kidney Function. (May 2015) - Devraj, Radhika; Borrego, Matthew; Vilay, A Mary; Gordon, Elisa J.; Pailden, Junvie; Horowitz, Bruce
Abstract: Aim: Low health literacy (HL) may contribute to poor self‐management of chronic kidney disease (CKD) and poor kidney function. This study aimed to assess the relationship between HL and estimated glomerular filtration rate (eGFR). Methods: A cross‐sectional observational study was conducted among consecutive eligible adult patients with CKD stages 1–4 attending an outpatient nephrology clinic. HL was assessed using Newest Vital Sign (NVS). eGFR was estimated using the Modification of Diet in Renal Disease equation. CKD self‐management behaviour knowledge was assessed using a study instrument (CKD self‐management knowledge (SMKT)). Results: One hundred fifty patients participated in the study (83% participation rate). The prevalence of high likelihood of limited HL was 32.7%. Participants' eGFRs ranged from 17 to 152 mL/min / 1.73 m 2, with over 80% of the eGFRs below 60 mL/min / 1.73 m 2 . HL was associated with eGFR after controlling for all demographics except age, race and gender (which are included in eGFR equation) ( P = 0.05). Every unit increase in NVS score was associated with a 1.9% increase (95% confidence interval = 0 to 3.86%) in eGFR (model R square = 0.23, P = 0.002), which remained significant after controlling for CKD‐SMKT ( P = 0.05; model R square = 0.28, P < 0.001). The relationship was non‐significant after controlling for age, although it remained significant after controlling for other demographics including gender and race. Conclusions: There is a small but significant association between HL and eGFR. Providers should use HL‐tailored communication strategies in CKD patients. Larger multicentre studies are needed to substantiate this relationship. Summary at a Glance: This study found a significant relationship between health literacy and renal function in patients with chronic kidney disease stages 1 through 4.